Tokoh dan Perbedaan Aliran Realisme Barat dan Timur Dalam perkembangan Kesusastraan Arab - Jannah, Raudhatul; Tasnimah, Tatik Maryatut (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
This study aims to describe the originators of western and eastern realism and the differences between western and eastern realism. The method used to describe the originators of the western and eastern realism schools and the differences between the western and eastern realism schools by using qualitative methods and collecting data using documentation techniques, namely library research. The results of this study are: First, the figures of Western realism are Gustave Flaubert, Guy De Maupassant. Second, realism figures in the East are Mahmud Taymūr, Taufiq El-Hakim, and Najib Mahfudz. Third, the West applies the concept of this flow to various genres of works of art such as painting, sculpture, fine arts, theater, novels and short stories. While the concept of realism in the East only applies this flow of realism to literary works in the form of novels, short stories, dramas and poetry.